MiR-181c level predicts response to exercise training in patients with heart failure and preserved ejection fraction: an analysis of the OptimEx-Clin trial. (11th September 2021) - Gevaert, Andreas B; Witvrouwen, Isabel; Van Craenenbroeck, Amaryllis H; Van Laere, Steven J; Boen, Jente R A; Van de Heyning, Caroline M; Belyavskiy, Evgeny; Mueller, Stephan; Winzer, Ephraim; Duvinage, André; Edelmann, Frank; Beckers, Paul J; et al.
Abstract: Aims: In patients with heart failure with preserved ejection fraction (HFpEF), exercise training improves the quality of life and aerobic capacity (peak V · O2 ). Up to 55% of HF patients, however, show no increase in peak V · O2 despite adequate training. We hypothesized that circulating microRNAs (miRNAs) can distinguish exercise low responders (LR) from exercise high responders (HR) among HFpEF patients. Methods and results: We selected HFpEF patients from the Optimizing Exercise Training in Prevention and Treatment of Diastolic HF (OptimEx) study which attended ≥70% of training sessions during 3 months ( n  = 51). Patients were defined as HR with a change in peak V · O2 above median (6.4%), and LR as below median ( n  = 30 and n  = 21, respectively). Clinical, ergospirometric, and echocardiographic characteristics were similar between LR and HR. We performed an miRNA array ( n  = 377 miRNAs) in 14 age- and sex-matched patients. A total of 10 miRNAs were upregulated in LR, of which 4 correlated with peak V · O2 . Validation in the remaining 37 patients indicated that high miR-181c predicted reduced peak V · O2 response (multiple linear regression, β = −2.60, P  = 0.011), and LR status (multiple logistic regression, odds ratio = 0.48, P  = 0.010), independent of age, sex, body mass index, and resting heart rate. Furthermore, miR-181c decreased in LR after exercise training ( P -group = 0.030, P -time = 0.048, P -interaction = 0.037). An in silico pathway analysis identified several downstream targets involved in exercise adaptation. Conclusions: Circulating miR-181c is a marker of the response to exercise training in HFpEF patients. High miR-181c levels can aid in identifying LR prior to training, providing the possibility for individualized management. Graphical Abstract: